EFL STUDENTS' PERCEPTION OF READING COMPREHENSION BY USING JIGSAW STRATEGY IN READING CLASS - Khoirunnisa Abdillah; Mansyur Srisudarso; Yogi Setia Samsi (IKIP Siliwangi, 2023)
This research aimed to investigate the perception how students feel about using the jigsaw method to teach them reading comprehension. The case study approach is being used in this descriptive qualitative research design. This research was conducted at one of the secondary school in West Java, Indonesia. All of the class VII A participants in this study participated, and 5 students were interviewed. The author employs observation as a method of gathering facts. Additionally, the author conducts semi-structured interviews with students to learn more about their viewpoints on using the jigsaw technique to teach reading comprehension. The qualitative method suggested by Miles & Huberman was used to analyze the data that has been obtained (1992:16). Three activity lines make up the analysis: data reduction, data display, and conclusion drawing/verification. The results showed that using the jigsaw method to learn reading comprehension, pupils feel happy and helpful when they cooperate with their group members. Keywords: Reading Comprehension; Jigsaw Strategy; Student Perception